A blueprint for symptom scales and responses: measurement and reporting. (13th April 2004) - Wyrwich, K W; Staebler Tardino, V M
Abstract : Measurement of symptom status among patients with GORD has, to date, been conducted in a variety of ways. We applied a cognitive psychology framework, as well as reviewed the current psychometric literature, to develop a blueprint for the best methods of measuring and reporting symptoms of patients with gastro-oesophageal reflux disease (GORD). Our review suggests that the seven point scale with word anchors for each point is likely to afford better reliability, improved sensitivity to change in GORD symptoms, and greater ease in administration compared with visual analogue or other types of response scales.